Artificial Intelligence in Marketing: A Bibliometric Mapping of Central and Eastern European Research - Németh, Renáta; Reicher, Zsuzsánna Regina; Majláth, Melinda (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The increasing adoption of artificial intelligence (AI) in marketing poses significant managerial and governance challenges, particularly for small and medium-sized enterprises (SMEs) operating in dynamic, digitally transforming markets. Although the academic literature on AI in marketing has expanded rapidly since 2020, the thematic structure of this research in the Central and Eastern European (CEE) context remains underexplored. This study aims to map AI-related marketing research in CEE countries. Keyword co-occurrence analysis and network visualisation were conducted using VOSviewer to identify dominant research themes, thematic interconnections, and emerging directions. The findings reveal interconnected thematic clusters addressing AI applications in marketing. The results highlight patterns in how AI-driven marketing and consumer trust are conceptualised in the CEE region. By offering a structured overview of the literature, this study supports a deeper understanding of AI-enabled marketing from a management perspective and provides a foundation for future research on AI adoption among SMEs.